Appropriateness of Biologics in the Management of Crohn's Disease Using RAND/UCLA Appropriateness Methodology. Issue 2 (19th October 2018) - Weizman, Adam V; Nguyen, Geoffrey C; Seow, Cynthia H; Targownik, Laura; Murthy, Sanjay K; Boland, Karen; Afzal, Nooran M; Khanna, Reena; Jones, Jennifer; Afif, Waqqas; Halder, Smita; Reinglas, Jason; et al.
Abstract: Background: 3 classes of biologics are now available for the treatment of Crohn's disease. The availability of multiple treatment options has led to questions regarding the appropriateness of each agent for a given patient. We aimed to evaluate physician preferences for the use of specific biologic agents in a variety of Crohn's disease management scenarios using the RAND/UCLA Appropriateness Methodology. Methods: A panel consisting of members of the CINERGI group (Canadian IBD Network for Research and Growth in Quality Improvement) was assembled. A literature review was performed on factors identified as influential upon choice of biologic therapy. Clinical scenarios were developed, and panelists rated the appropriateness of biologic therapy classes in each scenario individually and again during a face-to-face meeting after moderated discussion. Results: Two hundred eighty-eight modifications of 3 clinical scenarios were rated. Factors that influenced biologic choice included perianal disease, antidrug antibody status, extraintestinal manifestations, consideration of potential pregnancy, and history of serious infection or malignancy. Anti-TNF therapy was considered appropriate in the postoperative patient. Ustekinumab and vedolizumab were considered appropriate in patients without perianal disease over the age of 65 with a history of malignancy or serious infection. The use of anti-TNF therapy was considered inappropriate in some scenarios whereby drug level was adequate and no antidrug antibody (ADA) was detectable. Conclusions: We evaluated the appropriateness of the 3 available classes of biologics in a number of scenarios for the treatment of Crohn's disease. History of serious infection and malignancy, particularly in individuals over 65 years, and consideration of future pregnancy were patient-specific variables that impacted treatment decisions. These findings can serve as a guide for providers considering biologic therapy in patients with Crohn's disease. :